Prototype of an Auto Cutoff Battery Charging System Using Solar Panels - Mohamad Zainul Hasan (Pusat Publikasi Nusantara, 2025)
Solar panels are devices that convert solar energy into electrical power. The use of solar panels is typically coupled with batteries for energy storage. While short charging times are desirable in battery power systems, improper charging can damage both the system and the battery. Batteries play a critical role as energy sources when sunlight intensity is low, making optimized charging essential for maximizing battery performance as energy storage devices. This study aims to design and evaluate a fast-charging battery controller with an automatic shutoff system using solar panels. The controller is based on constant current and voltage (CCV) control principles, utilizing a buck-boost converter to stabilize the solar panel output voltage at 5 volts. The research methodology involved designing a prototype system comprising a 5WP solar panel, XL6009 buck-boost converter, TP4056 charging module, and a 2400mAh Li-Po 18650 battery. Testing was conducted over three days in January 2025 in Angsana Village, South Kalimantan, with data collection at different time periods (08.00–11.00, 12.00–14.00, and 15.00–18.00 WITA) to evaluate system performance under varying solar irradiation conditions. The results demonstrate that the charging time for a 2400mAh battery is approximately 2–3 hours under optimal solar irradiation conditions. The controller exhibits high accuracy and effectively prevents overcharging. The system employs a dual-indicator mechanism: a red LED illuminates during the charging process, while a blue LED activates when the battery reaches full charge or when the auto-cutoff mode engages at 4.2 volts.